Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/bot.0000000000001432
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fracture Energy With Sanders Classification and Post-traumatic Osteoarthritis After Displaced Intra-articular Calcaneus Fractures

Abstract: Objectives: To quantify fracture severity for a series of displaced intra-articular calcaneal fractures (DIACFs) and correlate it with Sanders classification, post traumatic osteoarthritis (PTOA), and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…e blood circulation, skin color, and temperature of the patient's foot were monitored, and antibiotics were administered to prevent infection [11,12]. e patients received insulin injections and their blood glucose was determined thrice daily for the adjustment of their insulin dose.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…e blood circulation, skin color, and temperature of the patient's foot were monitored, and antibiotics were administered to prevent infection [11,12]. e patients received insulin injections and their blood glucose was determined thrice daily for the adjustment of their insulin dose.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…The Sanders classification is still the most commonly used classification system today and is one of the most predictive of clinical outcomes. 20 , 24 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…The Sanders classification is still the most commonly used classification system today and is one of the most predictive of clinical outcomes. 20,24,26 One year later, Sanders published "Operative Treatment in 120 Displaced Intraarticular Calcaneal Fractures. Results Using a Prognostic Computed Tomography Scan Classification," which is the most cited article in the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Böhler's angle, a surrogate for the amount of energy absorbed by the foot, is considered a reliable tool for estimating the severity of the injury in calcaneal fractures and for estimating patient satisfaction 2 years post-trauma [10][11][12]. Previous studies have demonstrated a relationship between high-energy injury mechanisms and fracture complexity or accompanying soft tissue damage in various types of fractures, including calcaneal fractures and fractures of the ankle [13,14]. In such cases, prolonged pre-and postoperative soft tissue monitoring or further surgical interventions may be required.…”
Section: Discussionmentioning
confidence: 99%